Isolation and characterization of cytosolic malate dehydrogenase from Trichomonas vaginalis - Drmota, T; Tachezy, J; Kulda, J (Folia parasitologica, 1997)
Malate dehydrogenase (EC 1.1.1.37.) (MDH) was purified to apparent homogeneity from the cytosolic fraction of the protozoan Trichomonas vaginalis Donné. The four step purification included ion-exchange chromatography (DEAE-Sephacel and Q-Sepharose, elution with NaCl) and affinity chromatography (Reactive Red Agarose, elution with NADH and NaCl). The enzyme was purified about 132-fold (30.6% yield) to a specific activity of 352 units mg-1. The Km values determined at pH 7.8 (pH optimum from 7.5 to 8.3) for oxaloacetate and NADH were 16.2 microM and 10.6 microM, respectively. The MDH activity was inhibited by the substrate, decreasing to 50% at about 1 microM concentration of oxaloacetate. The reverse reaction from malate to oxaloacetate showed a pH optimum around pH 9.5. The Km for malate and NAD+ (determined at pH 7.8) were 1220 microM and 69.9 microM, respectively. SDS-PAGE analysis of the purified MDH revealed a single band with an apparent size of 34.5 kDa. The native molecular weight was estimated by HPLC gel filtration to be 60 kDa, which indicates that the T. vaginalis MDH exists as a dimer.
Keywords: Trichomonas vaginalis; Animals; cytosol; Enzyme Inhibitors; Oxaloacetates; Cytosol; malátdehydrogenasa; zvířata; molekulová hmotnost; Kinetics; oxalacetáty; Molecular Weight; Malate Dehydrogenase; koncentrace vodíkových iontů; NAD; Hydrogen-Ion Concentration; kinetika; inhibitory enzymů